The Implementation of the Merdeka Curriculum in Islamic Religious Education at SMPN 1 Pagar Alam - Rita Yulia Anggraini; Anugrah Hafid Rahmadani; Anugerah Syarifah Oktariah; Destiliana Amalta Putri; Duwi Nurhidayah; Isrok Afdilah; Ririn Hikmawati (The Future of Education Journal, 2024)
This curriculum change encourages a shift in the paradigm of curriculum and learning. It strengthens the independence of teachers as the main controllers in the learning process, loosens overly rigid standard controls, and demands a homogeneous learning process across all educational units in Indonesia, while enhancing student agency. The aim of this research is to explore how the implementation of the Merdeka Curriculum affects Islamic Religious Education (IRE) learning, as well as the quality of the Merdeka Curriculum in IRE learning in Class VIII at SMP Negeri 1 Pagaralam. The research method used in this study is descriptive qualitative research. Based on the results of observations and interviews conducted at SMP Negeri 1 Pagaralam, it can be concluded that there are two curricula applied: the Merdeka Curriculum for Classes VII and VIII, and the 2013 Curriculum for Class IX.